Maintenance of Nef-Mediated Modulation of Major Histocompatibility Complex Class I and CD4 after Sexual Transmission of Human Immunodeficiency Virus Type 1 - Noviello, C. M. (American Society for Microbiology, 2007)
Viruses encounter changing selective pressures during transmission between hosts, including host-specific immune responses and potentially varying functional demands on specific proteins. The human immunodeficiency virus type 1 Nef protein performs several functions potentially important for successful infection, including immune escape via down-regulation of class I major histocompatibility complex (MHC-I) and direct enhancement of viral infectivity and replication. Nef is also a major target of the host cytotoxic T-lymphocyte (CTL) response. To examine the impact of changing selective pressures on Nef functions following sexual transmission, we analyzed genetic and functional changes in nef clones from six transmission events. Phylogenetic analyses indicated that the diversity of nef was similar in both sources and acutely infected recipients, the patterns of selection across transmission were variable, and regions of Nef associated with distinct functions evolved similarly in sources and recipients. These results weighed against the selection of specific Nef functions by transmission or during acute infection. Measurement of Nef function provided no evidence that the down-regulation of either CD4 or MHC-I was optimized by transmission or during acute infection, although rare nef clones from sources that were impaired in these activities were not detected in recipients. Nef-specific CTL activity was detected as early as 3 weeks after infection and appeared to be an evolutionary force driving the diversification of nef. Despite the change in selective pressure between the source and recipient immune systems and concomitant genetic diversity, the majority of Nef proteins maintained robust abilities to down-regulate MHC-I and CD4. These data suggest that both functions are important for the successful establishment of infection in a new host.